Pengembangan Berpikir Kreatif Melalui Penguatan Kepercayaan Diri Mahasiswa - Sukenti, Desi (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2018)
ABSTRACT His study aims to determine the level of self-confidence of students of Indonesian language and literacy education programs and to know the influence of self-confidence in creative thinking of students. This research uses correlation method with simple linear regression analysis. The sample used is 132 students of Indonesian language and literature study program. The results showed that the students' confidence level was in the high category with the mean obtained (99.55). Based on the hypothesis test conducted to determine the effect of self-confidence to students' creative thinking obtained value (F = 49.273), value Sig. = 0.000 (P <0.05). This confirms that confidence has an influence on the creative thinking of the students of Faculty of Language and Literature Education Program. Based on statistical analysis, the research hypothesis is accepted, it means there is influence of self-confidence to creative thinking of Indonesian Language and Literature Education Study Program. The magnitude of the influence of self-confidence in student creative thinking illustrates that the value (R = 0.524a) and the value (R Square = 0.275). This shows that the magnitude of the influence of self-confidence is 0.275 which if it is minimized to be 27.5%, to the creative thinking of students of Indonesian Language and Literature Education Studies Program Faculty of Teacher Training and Education Islamic University of Riau.